Comparative analysis of environmental impacts of wheat and potato production in conventional and organic systems - Małgorzata Holka; Jolanta Kowalska (Journal of Plant Protection Research)
Agricultural production has a direct impact on the environment, both by consuming natural resources and by generating hazards in the form of emissions of various substances into the environment. Increased demand for plant products on global food markets contributes to heightened environmental pressure on agriculture. Agriculture, along with other sectors, should adhere to sustainability principles. Ongoing global development hinges on achieving a balance between economic growth and natural resource conservation. To fulfill the goals of sustainable development, agriculture should strive to minimize energy and natural resources consumption, thereby reducing its environmental impact. In the above context, research on the environmental effects of different agricultural production systems is needed. The aim of this study was to assess the environmental effects of two cultivation systems, conventional and organic, throughout the life cycles of winter wheat and potato production. The research employed a life cycle assessment (LCA) methodology from cradle to farm gate for assessing environmental impacts of crop cultivation across different farming systems, with respect to the functional unit of 1 tonne. Organic farming was shown to have lower environmental impacts than a conventional production system. The results confirm the sustainable nature of organic farming and its ability to mitigate the effects of farming activities. The LCA of conventional wheat and potato production showed that fertilizer application was the main environmental concern, highlighting the need to optimize fertilization to reduce environmental impacts. Furthermore, the results indicated that acidification and depletion of abiotic fossil fuel resources were significant environmental threats within the systems analyzed.